Muzyka i idee Pawła Szymańskiego. O książce Natalii Szwab - Nowicka-Ciecierska, Magdalena (Res Facta Nova, 2022)
Paweł Szymański’s works stand out as highly original against the background of Polish and world music. They have been performed throughout the world and have been the subject of reviews by music critics much more often than the subject of scholarly monographs. This article is a review of Natalia Szwab’s book Surkonwencjonalizm Pawła Szymańskiego. Idee i muzyka (Kraków 2020) – the first extensive monograph on the works of Szymański. In it the author presents the ideas which influenced these works, as well as detailed analyses of selected compositions (seventeen in total). She also provides a wide perspective on the composer’s self-reflections, while also presenting an objectivised discourse on his music through the use of aptly chosen quotations from the works of Polish musicologists, theorists and music critics. Authorial analyses of specific compositions demonstrate that, while Szymański’s scores contain perceptible rules, their actual effect escapes unambiguous interpretation. The author interprets Szymański’s works through the prism of postmodernist thought, including the techniques of deconstruction, intertextual strategies and surconventionalism. Undoubtedly a valuable attribute of this book is its presentation of Szymański’s music from different perspectives; the author demonstrates that in the same compositions one can observe different aspects of postmodernism which, as she says, “in a sense lead to the conception of surconventionalism formulated by the composer”.